1956
DOI: 10.1002/cber.19560890805
|View full text |Cite
|
Sign up to set email alerts
|

Der Übergang von Δ1‐Piperidein in Tetrahydro‐anabasin unter zellmöglichen Bedingungen

Abstract: Während Δ1‐Piperidein (I) in wäßriger Lösung im pH‐Bereich 9–12 bei 25° nur zu 2/3 in Tetrahydro‐anabasin (III) übergeht, weil dieses hier mit unverändertem Δ1‐Piperidein zu Isotripiperidein zusammentritt, geht es im pH‐Bereich 3–8 bei 25° bis zu 88% d. Th. in Tetrahydro‐anabasin über. Die Geschwindigkeit dieser auf den pH‐Bereich 3–12 beschränkten Reaktion ist außerordentlich stark pH‐abhängig, wofür eine Theorie gegeben wird. Die unter zellmöglichen Bedingungen so leicht erfolgende Bildung des Tetrahydro‐ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Indeed, Schöpf et al [10,11] have shown that the trimer 10 is stable at pH values above 12, whereas at pH values below 2 the monomer 9 is quickly formed. Moreover, they observed that ∆ 1 -piperideine dimerises to form tetrahydroanabasine (14), which may further react with a third molecule of 9 to generate trimer 13.…”
Section: Synthesis Of the Key Intermediates 8 And 11mentioning
confidence: 99%
“…Indeed, Schöpf et al [10,11] have shown that the trimer 10 is stable at pH values above 12, whereas at pH values below 2 the monomer 9 is quickly formed. Moreover, they observed that ∆ 1 -piperideine dimerises to form tetrahydroanabasine (14), which may further react with a third molecule of 9 to generate trimer 13.…”
Section: Synthesis Of the Key Intermediates 8 And 11mentioning
confidence: 99%
“…Many variations are possible for a route leading to matrine from a Clo unit, tetrahydroanabasine (13), and a C, unit, A'-piperideine (5), which are consistent with model A (Scheme 3). Three of these variations are outlined in Scheme 4.…”
Section: The Biosynthesis Of Matrinementioning
confidence: 74%
“…In aqueous solution at pH 6-8, A'-piperideine dimerizes readily and within a few hours 80-90% of the compound has been converted into dimer (13 of the dimer have the same molar specific activity, i.e. each of the labelled carbon atoms contains 50% of the activity of the intact molecule.…”
Section: The Biosynthesis Of Matrinementioning
confidence: 99%
“…This can be best appreciated in the work of Schçpf who investigated the formation of tetrahydroanabasin (26) from tetrahydropyridine 25. [22] In line with these studies, the large number of the stable isolable cyclic imines possess a,a-disubstitution; precluding the formation of the corresponding enamine and subsequent oligomerisation.…”
Section: Introductionmentioning
confidence: 77%